Does Work Stress Harm Job Performance? A Survey Study among Young Urban Professional Group (YUPPIES) - Mohd Noor, Nurul Hidayana; Kamal, Nur Balqis; Aminuddin, Nurhafizah (Journal of Human Capital Development (JHCD), 2019)
The main aim of this comparative study is to determine the influence of work stress towards job performance. A quantitative survey of 200 Malaysian young urban professional groups (YUPPIES) has been conducted. The main analysis first reveals that there is no relationship between extrinsic effort and job performance (r = 0.147, p = 0.145) for female YUPPIES and also for male YUPPIES (r = 0.038, p = 0.707). Second, there is significant and positive relationship between extrinsic reward and job performance for both female (r = 0.550, p = 0.000) and male (r = 0.399, p = 0.000) YUPPIES. Finally, there is no relationship between overcommitment and job performance (r = 0.117, p = 0.248) for female YUPPIES. However, there is significant and positive relationship between overcommitment and job performance (r = 0.423, p = 0.000) for male YUPPIES. Based on the findings, two interesting results have been discovered. First, extrinsic reward does not negatively affect performance for both gender and second, overcommitment does not negatively affect performance for female YUPPIES. Therefore, in this case, work stress has been discovered to give positive influence on job performance. These works illustrate and provide some views in organizational management and human capital development from Malaysian working environment.